Optimalisasi Penguasaan Materi Kesebangunan Melalui Pendekatan Problem Based Learning Pada Peserta Didik Kelas IX SMP - Prasetyawati Prasetyawati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
This study aims to determine the optimization of mathematics mastery through a problem based learning approach in Mathematics learning. Subjects and data sources of the study were 34 students. Methods of collecting data using observation, documentation, and tests. Data analysis uses critical and comparative analysis. The percentage of learning completeness obtained in the cycle is 38% and in the first cycle is 74% and the second cycle is 100%. Thus, the learning achievements of students in mathematics learning from pre-cycle up to the second cycle had a significant increase.